2000
DOI: 10.1046/j.1525-142x.2000.00077.x
|View full text |Cite
|
Sign up to set email alerts
|

Molluscan engrailed expression, serial organization, and shell evolution

Abstract: Whether the serial features found in some molluscs are ancestral or derived is considered controversial. Here, in situ hybridization and antibody studies show iterated engrailed-gene expression in transverse rows of ectodermal cells bounding plate field development and spicule formation in the chiton, Lepidochitona cavema, as well as in cells surrounding the valves and in the early development of the shell hinge in the clam, Transennella tantilla. Ectodermal expression of engrailed is associated with skeletoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
105
3

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(125 citation statements)
references
References 39 publications
17
105
3
Order By: Relevance
“…This latter hypothesis (Text- fig. 4A) is supported by evolutionary development studies, which have demonstrated that shell development in the chiton Lepidochitona is associated with the ectodermal expression of the engrailed gene (Jacobs et al 2000). Engrailed is also associated with valve development in bivalves and gastropods, and with skeletal development in many other metazoan phyla.…”
Section: A F F I N I T I E S a N D S I G N I F I C A N C E F O R M O mentioning
confidence: 89%
See 1 more Smart Citation
“…This latter hypothesis (Text- fig. 4A) is supported by evolutionary development studies, which have demonstrated that shell development in the chiton Lepidochitona is associated with the ectodermal expression of the engrailed gene (Jacobs et al 2000). Engrailed is also associated with valve development in bivalves and gastropods, and with skeletal development in many other metazoan phyla.…”
Section: A F F I N I T I E S a N D S I G N I F I C A N C E F O R M O mentioning
confidence: 89%
“…Engrailed is also associated with valve development in bivalves and gastropods, and with skeletal development in many other metazoan phyla. Jacobs et al (2000) interpreted this as evidence for a single evolutionary origin of the invertebrate skeleton, which would imply that valves were primitive not only to the Aculifera but to the Mollusca as a whole. Scheltema (1993Scheltema ( , 1996 regarded the eight-fold 'pseudometamerism' of the monoplacophorans (see Wingstrand 1985) as primitive to the Mollusca but generally reduced in the Aculifera (Text-fig.…”
Section: A F F I N I T I E S a N D S I G N I F I C A N C E F O R M O mentioning
confidence: 99%
“…For instance, if an organism displays brooding behaviour, large numbers of embryos can be obtained by locating reproducing individuals [85,86]. Such individuals can be brought alive to the lab and manipulated for fixation.…”
Section: Embryonic Tissuesmentioning
confidence: 99%
“…Many regulatory genes encoding transcription factors and signalling molecules are expressed in the shell field in conchiferans (Moshel et al 1998, Jacobs et al 2000, Klerkx et al 2001, Wanninger and Haszprunar 2001, Nederbragt et al 2002, Hinman et al 2003, Baratte et al 2007, Koop et al 2007, Ijima et al 2008, Shigeno et al 2008, Grande and Patel 2009, Kin et al 2009, Samadi and Steiner 2009, Kurita and Wada 2011, Shimizu et al 2011, Hashimoto et al 2012, Shimizu et al 2013. The function of many of these genes remains unknown.…”
Section: The Mantle Appears To Use Conserved Developmental Regulatorsmentioning
confidence: 99%
“…The function of many of these genes remains unknown. However, extensive comparisons of engrailed gene expression patterns amongst different molluscs suggest that this gene has a role in the formation of a compartment boundary by delimitating the shell field margin that secretes the protoconch (Moshel et al 1998, Jacobs et al 2000, Wanninger and Haszprunar 2001, Nederbragt et al 2002, Ijima et al 2008, Shigeno et al 2008. In contrast, decapentaplegic (dpp) expression patterns are not conserved among molluscs, with functions ranging from the proliferation of cells around the shell gland to the control of shell shape and coiling growth (Nederbragt et al 2002, Koop et al 2007, Ijima et al 2008, Kin et al 2009, Shimizu et al 2011, Hashimoto et al 2012, Shimizu et al 2013.…”
Section: The Mantle Appears To Use Conserved Developmental Regulatorsmentioning
confidence: 99%